# Invertible matrices problem

## Homework Statement

For the invertible matrices A, B and A-B, simplify the expression $$(A - B)^{-1}A(A^{-1} - B^{-1})B$$.

## Homework Equations

properties of invertible matrices

## The Attempt at a Solution

$$(A - B)^{-1}A(A^{-1} - B^{-1})B$$
= $$(A - B)^{-1}(AA^{-1}B - AB^{-1}B)$$
= $$(A - B)^{-1}(IB - AI)$$
= $$(A - B)^{-1}(B - A)$$
= $$I$$

Am I correct?

Related Calculus and Beyond Homework Help News on Phys.org
vela
Staff Emeritus
Homework Helper
Almost. The last step isn't quite correct.

LCKurtz
Homework Helper
Gold Member
Verrrry close. Check your last step.

So it just ends here?

$$(A - B)^{-1}(B - A)$$

vela
Staff Emeritus
Homework Helper
No, you can simplify it. Consider this. Let C=B-A. Then C-1=(B-A)-1, but in your expression, you have (A-B)-1, which isn't the same matrix.

No, you can simplify it. Consider this. Let C=B-A. Then C-1=(B-A)-1, but in your expression, you have (A-B)-1, which isn't the same matrix.
Ok, so then the answer is:

$$-I$$ ?

LCKurtz